2007
DOI: 10.1016/j.ccr.2006.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Neuropilin-1 Function Has an Additive Effect with Anti-VEGF to Inhibit Tumor Growth

Abstract: Neuropilin-1 (NRP1) guides the development of the nervous and vascular systems. Binding to either semaphorins or VEGF, NRP1 acts with plexins to regulate neuronal guidance, or with VEGFR2 to mediate vascular development. We have generated two monoclonal antibodies that bind to the Sema- and VEGF-binding domains of NRP1, respectively. Both antibodies reduce angiogenesis and vascular remodeling, while having little effect on other VEGFR2-mediated events. Importantly, anti-NRP1 antibodies have an additive effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

46
531
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 493 publications
(583 citation statements)
references
References 55 publications
46
531
1
5
Order By: Relevance
“…A humanized anti-VEGF antibody (Avastin V R ; Genentech, Inc.) is currently approved for treatment of multiple human cancers. The anti-NRP1 B antibody blocks VEGF binding to the NRP1 receptor and has been shown to inhibit vascular sprouting (34) and have an additive effect with anti-VEGF in inhibiting tumor growth (35). In this study, both therapies exhibited significant effects on blood volume and Q of varying degrees.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…A humanized anti-VEGF antibody (Avastin V R ; Genentech, Inc.) is currently approved for treatment of multiple human cancers. The anti-NRP1 B antibody blocks VEGF binding to the NRP1 receptor and has been shown to inhibit vascular sprouting (34) and have an additive effect with anti-VEGF in inhibiting tumor growth (35). In this study, both therapies exhibited significant effects on blood volume and Q of varying degrees.…”
mentioning
confidence: 71%
“…The anti-VEGF molecule used in this study is known to be a potent antibody to VEGF and has previously been shown to inhibit tumor growth (31), reduce vascular density (7), and reduce the dynamic contrast-enhanced-MRI parameter K trans (33). The second molecule used in this study, anti-NRP1 B , has also been shown to inhibit vascular density (34) and to slow tumor growth when used in combination with anti-VEGF (35). The comparison of the vascular effects of these two molecules demonstrates that this MRI vascular imaging technique is capable of detecting statistically significant results for both strong angiogenic inhibitors and more subtle antiangiogenic antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several anti-neuropilin-1 agents that blocked VEGF binding were tested in animal models (Pan et al, 2007). Our findings on GBM cells suggest an additional role for neuropilin-1, in which it acts as a Sema3A receptor and facilitates tumor cell dispersal.…”
Section: Discussionmentioning
confidence: 65%
“…Recently, peptidic antagonists of NRP1 have been successfully used to block Sema3A signaling (Williams et al, 2005). Moreover, function blocking antibodies to NRP1 reduce tumor growth (Pan et al, 2007), and selective inhibitors of Sema3A improve nerve regeneration (Kaneko et al, 2006). The hydrophobic character of the pTM-NRP1 offers a unique chance to target naturally the heart of the cell membrane and thereby to increase the probability of inter-action with the protein domains to modulate.…”
Section: Discussionmentioning
confidence: 99%